PERAN PEMERINTAH DALAM MEMBERIKAN DANA INSENTIF GUNA MENDUKUNG PEMBANGUNAN EKONOMI KREATIF DAERAH (Universitas Suryakancana, 2019)
With the enactment of the ASEAN Free Trade Area (AFTA) and the ASEAN Economic Community (AEC) in early 2016, global markets between ASEAN regions are increasingly open and competition between countries is very tight in marketing their creative economy products or services. These conditions, spurred the Indonesian people including the Cianjur Regency Government to increase and take advantage of business opportunities through the development of a relative economy in order to increase regional economy. But the development of the creative economy is hampered in getting funding support. In connection with this, what is the background of the Cianjur regency government to develop creative economic policies and how government support in providing access to capital in developing the regional creative economy. In order to examine this problem, the method used is juridical normative approach, by studying the principles of law, especially positive legal rules that have a relationship with the problem that is the object of research. Keywords: Creative Economy; Era of Globalization; Incentive Funds.